2021
DOI: 10.1371/journal.pone.0248827
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of lung ultrasound for transient tachypnea of the newborn: A meta-analysis

Abstract: Several recent studies demonstrated that lung ultrasound could achieve desired diagnostic accuracy for transient tachypnea of the neonate (TTN). However, the diagnostic performance of lung ultrasound for TTN has not been systematically studied to date. This meta-analysis aimed to investigate the performance of lung ultrasound in diagnosing TTN. The relevant literature was searched in PubMed, Medline, the Cochrane Library, and Embase databases without any restriction in terms of language and time until January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…This meta-analysis was novel in evaluating the accuracy and diagnostic value of POCUS for detecting ETT and assessing its placement. Previous meta-analysis studies described the diagnostic performance of POCUS regarding transient tachypnea of the newborn (TTN) ( 44 , 45 ), respiratory distress syndrome (RDS) ( 46 ) and bronchopulmonary dysplasia (BPD) ( 47 ). The pooled results obtained from the selected studies demonstrated that POCUS can recognize ETT in 96.8% of cases and describe its correct placement with a pooled sensitivity of 93.44% ranging from 0.71 to 1.00.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis was novel in evaluating the accuracy and diagnostic value of POCUS for detecting ETT and assessing its placement. Previous meta-analysis studies described the diagnostic performance of POCUS regarding transient tachypnea of the newborn (TTN) ( 44 , 45 ), respiratory distress syndrome (RDS) ( 46 ) and bronchopulmonary dysplasia (BPD) ( 47 ). The pooled results obtained from the selected studies demonstrated that POCUS can recognize ETT in 96.8% of cases and describe its correct placement with a pooled sensitivity of 93.44% ranging from 0.71 to 1.00.…”
Section: Discussionmentioning
confidence: 99%
“…The LUS score for the prediction of RDS showed 80.2% sensitivity and 100% specificity using a cut-off of 21.5 (AUC = 0.938) [ 16 ]. LUS showed better performance in the diagnosis of RDS; for diagnosing RDS with pooled sensitivity of 0.99 and a specificity of 0.95 and for TTN with pooled sensitivity of 0.67 and specificity of 0.97 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observation indexes included pleural lines, A-lines, B-lines, lung consolidation with air bronchograms, shred signs, and pleural effusion. These were defined as follows [ 11 ]: (1) Pleural line: the regular echogenic line under the superficial layers of the thorax moving continuously during respiration, while abnormal pleural lines refer to pleural line disappearance, thickening, irregularity, or a coarse and indistinct appearance. (2) Lung sliding: in real-time ultrasound, we find that the pleural line moves in a to-and-fro pattern, synchronized with respiratory movement, which is called lung sliding.…”
Section: Methodsmentioning
confidence: 99%
“…Timely and accurate diagnosis is important to enable efficient treatment and improve the prognosis of patients with neonatal pneumonia. Recently, lung ultrasound (LUS) has been successfully used to diagnose several kinds of neonatal lung diseases, such as meconium aspiration syndrome (MAS) [ 6 , 7 ], respiratory distress syndrome (RDS) [ 8 , 9 ], transient tachypnea of newborn (TTN) [ 10 , 11 ], pneumothorax [ 12 , 13 ], pulmonary hemorrhage [ 14 ], bronchopulmonary dysplasia (BPD) [ 15 ], bronchiolitis [ 16 ], and congenital lung malformation [ 17 , 18 ]. LUS has especially been widely used in the diagnosis of neonatal pneumonia, including bacterial or viral pneumonia, but not including fungal pneumonia [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%